The comorbidities of diarrhea and acute respiratory tract infection and risk factors among under-five children in 45 low- and middle-income countries - Berhan Tekeba; Deresse Abebe Gebrehana; Enyew Getaneh Mekonnen; Alebachew Ferede Zegeye; Chilot Kassa Mekonnen; Hailemichael Kindie Abate; Tewodros Getaneh Alemu; Mulugeta Wassie (Scientific Reports)
Abstract Diarrhea and acute respiratory tract infections (ARIs) are the primary causes of morbidity and mortality in children under the age of five worldwide. However, there is a scarcity of up-to-date conclusive multi-country studies on the comorbidity of diarrhea and acute respiratory tract infection in under-five children in low- and middle-income countries. Therefore, this study aimed to assess the pooled magnitude and contributing factors of comorbidity of diarrhea and acute respiratory tract infection in low- and middle-income countries. A cross-sectional study design was employed with the most recent Demographic and Health Survey secondary data (DHS) from 2015 to 2024 in low- and middle-income countries. This secondary data was accessed from the DHS portal through an online request. The DHS is the global data collection initiative that provides detailed and high-quality data on population demographics, health, and nutrition in low- and middle-income countries. We used a weighted sample of 669,138 children aged 0–59 months. A multilevel mixed-effect binary logistic regression model was fitted to identify significant factors associated with comorbidity of diarrhea and ARI. The level of statistical significance was declared with a p-value < 0.05. This study found that 5.44% (95% CI: 5.38–5.49) of under-five children in low- and middle-income countries developed a comorbidity of diarrhea and acute respiratory tract infection. Maternal age, child age, wealth index, child sex, birth size, media exposure, vaccination status, health insurance, survey year, residence, country income level, and geographic region were significantly associated with the comorbidity of diarrhea and acute respiratory infection. This study revealed that a sizable portion of under-five children developed a comorbidity of diarrhea and ARI in low- and middle-income countries. Both individual and community-level factors are significantly associated with the comorbidity of diarrhea and ARI. Therefore, the World Health Organization, with its partners, should inform respective countries executives and policymakers to focus on younger children, teenage mothers, media coverage, clean water provision, childhood vaccination, and extreme birth-weight babies. Moreover, low- and middle-income countries are encouraged to strengthen health insurance coverage, expand healthcare infrastructure, pursue sustainable economic growth, and foster intergovernmental collaboration to mitigate the comorbidity of diarrhea and acute respiratory tract infections.